Influence of traffic on the temperature field of tunnel in cold region: A case study on the world's longest highway spiral tunnel - Yifan Jiang; Jianyou Yu; Ping Zhou; Feicong Zhou; Jiayong Lin; Jinyi Li; Ming Lin; Feiya Lei; Zhijie Wang (Underground Space, 2023)
The impact of the piston wind caused by vehicle traffic on the temperature field distribution of the tunnel cannot be ignored, especially in spiral tunnels, where the temperature field distribution is more complicated than that in straight tunnels. Based on the world's longest highway spiral tunnel, this study explores the influence of traffic on the temperature fields of spiral and straight tunnels, and proposes a new design method for laying length of insulation layer. The results show that traffic has a significant effect on the temperature field distribution in the tunnel. The influence degree of different traffic elements decreases in the following order: average vehicle speed > daily traffic > morning rush hour > evening rush hour. The temperature field distribution of spiral tunnels is asymmetry on the left and right compared with straight tunnels, while the influence degree of traffic on the outside of spiral tunnels is similar to that of straight tunnels. Due to the difference of wind direction and traffic direction at different tunnel openings, an asymmetric insulation layer laying method is proposed. It is suggested that the lengths of the insulation layers of the Jinjiazhuang Tunnel should be 1200 m for the right tunnel inlet, 700 m for the right tunnel outlet, 700 m for the left tunnel inlet, and 1400 m for the left tunnel outlet.